2014
DOI: 10.1038/nature13897
|View full text |Cite
|
Sign up to set email alerts
|

The participation of cortical amygdala in innate, odour-driven behaviour

Abstract: Innate behaviors are observed in naïve animals without prior learning or experience, suggesting that the neural circuits that mediate these behaviors are genetically determined and stereotyped. The neural circuits that convey olfactory information from the sense organ to the cortical and subcortical olfactory centers have been anatomically defined1-3 but the specific pathways responsible for innate responses to volatile odors have not been identified. We have devised genetic strategies that demonstrate that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
243
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(252 citation statements)
references
References 36 publications
(37 reference statements)
7
243
0
2
Order By: Relevance
“…Much like the experiments discussed above, this strategy has produced exciting results. For example, recent work deciphering the role of the cortical amygdala in odordriven behavior has shown that the after isolation of odor-related ensembles, activation of these neuronal populations in the absence of odor recapitulates responses observed previously during odor exposure (Root et al, 2014). Furthermore, using the same mouse model, deactivating fear-related neural circuits in the hippocampus inhibits freezing behavior after exposure to a fear-inducing context .…”
Section: B Isolation and Manipulation Of The Relapse Engrammentioning
confidence: 85%
“…Much like the experiments discussed above, this strategy has produced exciting results. For example, recent work deciphering the role of the cortical amygdala in odordriven behavior has shown that the after isolation of odor-related ensembles, activation of these neuronal populations in the absence of odor recapitulates responses observed previously during odor exposure (Root et al, 2014). Furthermore, using the same mouse model, deactivating fear-related neural circuits in the hippocampus inhibits freezing behavior after exposure to a fear-inducing context .…”
Section: B Isolation and Manipulation Of The Relapse Engrammentioning
confidence: 85%
“…1C and Fig. S4) (29)(30)(31)(32)35). Some odorant classes (azines, terpenes, thiols) included odorants with different behavioral effects whereas others (camphors and thiazoles) included only aversive odorants and still others (esters, ketones, and vanillin-like compounds) were uniformly neutral (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Innate odor responses, such as aversive responses to predator odors (3,21,23,(27)(28)(29)(30)(31)(32), are similar among individuals. The stereotyped nature of these responses suggests the existence of genetically determined neural circuits in which olfactory sensory input from a given receptor or combination of receptors has a high probability of eliciting a specific response.…”
mentioning
confidence: 99%
“…Moreover, photoactivation of these ensembles elicited approach and avoidance behaviours, respectively. Thus, the authors were able to identify neuronal representations in cortical amygdala that comprise determined neural circuits for the generation of innate olfactory responses [50].…”
Section: Innate Olfactory Behaviourmentioning
confidence: 99%
“…This connectivity has been proposed to provide an anatomical substrate for innate and learned olfactory behaviours, respectively. Root et al labelled and manipulated neurons responsive to innately appetitive and aversive odours by using the Arc promoter to drive expression of the light-activated cation channel, channelrhodopsin [50]. The authors injected an AAV encoding a Cre-dependent channelrhodopsin fused to enhanced yellow fluorescent protein (ChR2-EYFP) into the cortical amygdala of a transgenic mouse in which the Arc promoter drives the expression of a tamoxifen-dependent Cre-recombinase (CreER rstb.royalsocietypublishing.org Phil.…”
Section: Innate Olfactory Behaviourmentioning
confidence: 99%